Correlation Between Body Mass Index (BMI) and Fasting Total Blood Cholesterol Level among Undergraduate Students - Doustjalali, Saeid Reza; Dar, Hlaing Thaw; Zin, Khin Thant; Gujjar, Kumar Raghav; Sharma, Ratika; Jasman, Nabil Nuraiman; Bhaukaurally, Waseem; Sisay, Fatoumatta Laibo; Jin, Lim Sook; Hilmy, Izyan Yusoff; Lwin, Ye Kyaw; Al-Jashamy, Karim; et al. (Pakistan Journal of Nutrition, 2016)
A cross sectional study to observe the relation between body mass index (BMI) and the fasting total blood cholesterol level was carried out among 82 undergraduate medical students from SEGi University, Kota Damansara. The participants were randomly selected to participate in this research. The BMI was then calculated by using the standard formula (kg/m2). The fasting total blood cholesterol level was measured by using home cholesterol kit. The obtained data was then analyzed by using statistical package for the social sciences software (version 22.0). For males, the highest mean BMI value and highest mean fasting total blood cholesterol level were recorded for Indian students followed by Malays and Chinese. There was significant correlation between BMI and the fasting total blood cholesterol level in male participants (0.001, r-value = 0.525). As for females, Malays had the highest mean BMI value followed by Indians and Chinese and the highest mean fasting total blood cholesterol level was found in Chinese followed by Malays and Indians. No significant correlation was found between BMI and fasting total blood cholesterol levels in female participants (0.922, r-value = 0.015). However, there was a significant correlation between BMI and fasting total blood cholesterol level in overall male and female participants (0.015, r-value = 0.267). In conclusion, our study suggests that the students should be advised to exercise more; reduce intake of food with high cholesterol, avoid fast food and have an active and healthy lifestyle. This may overall improve their health status and prevent them from getting diseases which are associated with obesity and high cholesterol level.